Recommended Native Landscape Plants for Florida’s Treasure Coast - Sandra B. Wilson; Judith A. Gersony; Keona L. Nolan; Janice C. Broda; Edward A. Skvarch, Jr. (EDIS, 2013)
This 17-page fact sheet provides useful resources and handy tables for information on the function, form, and landscape use of proven native performers of the Florida Treasure Coast (Martin, St. Lucie, and Indian River Counties). Written by Sandra B. Wilson, Judith A. Gersony, Keona L. Nolan, Janice C. Broda, and Edward A. Skvarch, Jr., and published by the UF Department of Environmental Horticulture, March 2013.